Effort To Manage Waste Effectively And Educatively With Alternative Waste Banks As A Solution In The Villange Of Ngujuran Bancar - Rosyidah, Irma (SERUNAI, 2021)
The waste bank is collective dry waste management system that encourages the community to play an active role in it. This system will accommodate, sort, and distibute economic value waste to the market so that the community can benefit economically from saving waste. Waste bank as the implementation of 3R (Reuse, Reduce. Recycle) strategy in waste management at the source at the community level with a pattern of economic incentives. Garbage that accumulates couses pollution to the environment, causing diseases that will spread to the community. The lack of participation factors, including a lack of responsibility and low knowladge about the environment. So that people do not understand the negative impact given by a dirty and slum environment. The purpose of this studof data is to describe how to manage waste effectively and educatively with an alternative waste bank as solution in Ngujuran vilage. This research that the author did is included in a descriptive study with a quakitative approach. Type of data obtained through interviews with the community and direct observatin. In this assitance, researchers use the PAR (Participatory Action Research) method. PAR consists of words that are related to each other. The rhree words are participation, research and action. In PAR activities, reseachers learn and work together with the communty in making changes. The resulth of the study indicate that the implementation of assistence to the community obtained after taking action on the community is expected to be able to build awareness and participate in protecting the environment. Minimize the circulation of waste bank, the people of Ngujuran vilage realized how important it was to maintain environment health and cleaknliness. This effort is not easy, but the people of Ngujuran Vilangge are very enthusitic in supporting this mentoring process.